Dialectics of Transnational Mobility, Class, and Cultural Intermediary among Indonesian Migrant Worker-Students in South Korea - Muna Yastuti Madrah; Suharko Suharko; Diana Dewi Sartika (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2021)
Cosmopolitanism among migrant workers may present the result of interpretations between transnational mobility, class, and cultural intermediary. The purposes of this study describe the dynamics of travel and immigration, and higher education experiences that have let Indonesian migrant workers at work in any place both in and out of campus areas and how the transformational processes of the migrant worker from transnational into cosmopolitan. Applying the ethnographic method this research was carried out during 2018-2019, which took Indonesian migrant worker-students aged 20-35 years in South Korea as informants. This research found that the broader social, cultural, and individual agendas are one way of recognizing a new cosmopolitanism. There are two factors that influence the cosmopolitanism process of Indonesian migrant workers; first, the transnational migration process. Second, the process of cultural intermediation in universities. This study reveals significant differences in how Indonesian migrant workers respond to the possibilities and opportunities of transnational mobility, from developing the cultural acceptance skills needed in their life trajectories to building network relationships with other transnational actors. Higher education for migrant workers has introduced another form of work, namely cultural intermediation, which can be seen as a cosmopolitan process._________The original draft of this article has been presented on the International Conference on Language, Linguistics, and Literature (COLALITE) UNSOED, 2020.